The landscape formation history based on the detailed geological investigation in Aribaya and surrounding area, Pangetan district, Banjarnegara regency, Central Java - Annisa Helly Suranda; Huzaely Latief Sunan; Indra Permanajati (Journal of Earth and Marine Technology (JEMT), 2022)
The research site is in the Aribaya area and surrounding areas with an area of 16 km2 which is administratively included in Pagentan Subdistrict, Banjarnegara Regency, Central Java Province. The research area consists of 13 villages, namely: Suwidak, Pandansari, Karangtengah, Gumingsir, Karangnangka, Aribaya, Larangan, Talunamba, Clapar, Gununggiana, Pakelen, and Nagasari. Research objects in the form of Geomorphology, Stratigraphy, Geological Structure, Geological History, and Geological Potential. The geomorphology of the research area is divided into the Aribaya Fault Zone Unit, Gununnggiana Lava Flow Ridge Unit, and Aribaya Intrusion Unit. Based on unofficial lithostratigraphic units, the research area is divided into three rock units and the order from old to young, namely: Sandstone - Claystone Distribution Unit, Pyroclastic Brection Unit, and Diorit Intrusion Unit. Precipitated Sandstone - Claystone In the middle-upper neritic bathymetry environment, which belongs to the formation of the early Miocene – Middle-aged vines. Furthermore, tectonic activity occurs that causes the research area to form faults and syncline folds. Then at the time of the Early Pliocene, there was an influence from the activity of Mount Maung which provided sediment supply in the form of andesite fragments and matrix-sized Tuff Crystals so as to form a pyroclastic breccia unit. At the Time of the Pliocene, there was also diorite intrusion. The next process is the exogenous process that causes morphological form as it is today. The geological potential contained in the research area in the form of diorite mining excavations (positive potential) and landslide movement (negative potential) is quite a lot in the research area.